Memerdekakan Peserta Didik pada Tingkat Sekolah Dasar (SD) - Ningrum, Mega Widya; Febriyani, Imelda; Febliya, Hanni; Ulfatari, Olla; H, Huryanti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Education in Indonesia is currently still colored by various problems, one of which is the lack of independence for students. This can be seen from the learning system that is still centered on teachers, a rigid curriculum, and assessments that only focus on cognitive aspects. This condition causes students to have no room to develop their potential and talents optimally. One effort to realize independent education is to develop an active and participatory learning culture. This can be done by using constructivist learning theory. The method used in this study is a literature study by collecting data from previous research results and their relevant results. The purpose of the literature study in this study is 1) to find the problem to be studied, 2) to find information and data that is relevant to the topic to be discussed, 3) to add new knowledge from the results of the research being studied, 4) to test a basic truth of the theoretical approach in the problem being studied. While the analysis technique used is content analysis. The results of this study indicate that constructivist learning theory is effective in liberating students (SD). Several previous studies have used this theory in dealing with the problem of restraint/restriction of learning in children. This is because this theory directs learning according to their nature, interests, and talents by directing the active role of students in building their own knowledge so that students can freely develop and process in learning.